Menyulam Kebhinekaan: Akselerasi Desa Moderat Dalam Bingkai Kehidupan Beragama Kampung Bima Merdeka - ., sofiah; Al Malahim, Ainul Churia; Hamdani, Korib; Pertiwi, Fenni Putri (LPPM Universitas Dharma Andalas, 2025)
Indonesia, as a country with cultural and religious diversity, has villages as important laboratories for strengthening interfaith tolerance. However, social, political, and economic dynamics have created complex challenges, including the potential for religious conflict. However, this is different in Sidomulyo Village, Lumajang, which is inhabited by a multi-religious community (Islam, Catholic, Christian, and Hindu) and multi-ethnic (Javanese and Madurese), serving as an important example in managing this diversity. This village also served as the inauguration site for the BIMA MERDEKA Village, an initiative to strengthen religious moderation and counter radicalism. The purpose of this community service was to analyze superior assets and asset development strategies and to identify outcomes of the asset development program. The method used was the ABCD (Asset-Based Community Development) approach through the 5-D cycle (Define, Discovery, Dream, Design, and Destiny). The results of the community service show that this village has interfaith harmony, local cultural potential, and high social participation. The development strategy involves collaboration between religious leaders and the community in designing programs based on local wisdom. This program has successfully increased awareness of religious moderation and become a model for sustainable diversity management.